Development of a population pharmacokinetic model to characterize the pharmacokinetics of intrathecally administered tominersen in cerebrospinal fluid and plasma - Yumi Yamamoto; Patricia Sanwald Ducray; Marcus Björnsson; Kevin Smart; Paul Grimsey; Suresh Vatakuti; Agnes Portron; Benoit Massonnet; Daniel A. Norris; Hanna E. Silber Baumann (Wiley, 2023)
Abstract Tominersen is an intrathecally administered antisense oligonucleotide targeting huntingtin mRNA which leads to a dose‐dependent, reversible lowering of cerebrospinal fluid (CSF) mutant huntingtin protein concentration in individuals with Huntington's disease. Nonlinear mixed‐effect population pharmacokinetic (PopPK) modeling was conducted to characterize the CSF and plasma pharmacokinetics (PK) of tominersen, and to identify and quantify the covariates that affect tominersen PKs. A total of 750 participants from five clinical studies with a dose range from 10 to 120 mg contributed CSF (n = 6302) and plasma (n = 5454) PK samples. CSF PK was adequately described by a three‐compartment model with first‐order transfer from CSF to plasma. Plasma PK was adequately described by a three‐compartment model with first‐order elimination from plasma. Baseline total CSF protein, age, and antidrug antibodies (ADAs) were the significant covariates for CSF clearance. Body weight was a significant covariate for clearances and volumes in plasma. ADAs and sex were significant covariates for plasma clearance. The developed PopPK model was able to describe tominersen PK in plasma and CSF after intrathecal administration across a range of dose levels, and relevant covariate relationships were identified. This model has been applied to guide dose selection for future clinical trials of tominersen in patients with Huntington's disease.